Experimental Study of the Phenomenon of Stability Loss of a Horizontal Thin-Walled Cylindrical Shell Loaded by a Liquid - Kacperski, T. (Engineering Transactions, 1994)
The cylindrical shell constituting the wall of a large horizontal test tank supported at its ends and filled with water is loosing its stability. The compressive stress loading to buckling and failure of the shell, which was loaded by the weight of its liquid contents, has been compared with the critical stress as determined from the empirical formula proposed by Donnell concerning a cylindrical shell subjected to axial compression. The agrement between the two values was found to be satisfactory.